Inclusive growth and decent jobs by gender: The case of urban areas in Bolivia - Beatriz Muriel Hernández; Sergio Mansilla (Institute for Advanced Development Studies (INESAD), 2023)
This study assesses the level of inclusiveness of the extraordinary growth experienced by Bolivia from 2006 to 2019 in terms of decent jobs generation in urban areas and by gender. We use the Ali and Son (2007) concentration of opportunities curves, the Cameron and Trivedi (2005) Bootstrap technique to estimate confidence intervals for measuring the robustness of differences in the results between years, and we establish proxies for decent jobs with five rates proposed by Muriel (2014, 2019, 2020a, 2020b); i.e. job stability, receiving the Christmas bonus, social protection, sufficient labor income, and labor association affiliation. The results show that growth was inclusive from 2006 to 2011, but not afterwards. The percentage of workers with the Christmas bonus, sufficient labor income and affiliation to a labor association were lower in 2019 compared to 2006. As for the gender gaps, the one associated with sufficient labor income stands out, but the main problems lie in the inequities of access to opportunities within the same female population.
Keywords: D63; J16; J29; J39; J83; 330; decent jobs; inclusive growth; gender